Efektivitas Program Bantuan Sosial Sebagai Sarana Kebijakan Ekonomi Publik - Nurahman, Rifki; Hermawati, Anira Syifaa Putri; Wahdah, Nurul; Alfiah, Silvi; Afiyah, Najla; Hardiansyah, Dika; Helmi, Luthfi; Herdiana, Dian (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Social assistance programs are an important public economic policy instrument in the government's efforts to improve the welfare of the community, especially the vulnerable and poor. Through various programs such as the Family Hope Program (PKH), social assistance is expected to reduce poverty, improve access to education and health services, and ease the economic burden on beneficiaries. This study aims to analyze the effectiveness of social assistance programs as a means of public economic policy, by identifying the obstacles faced and the impact felt by beneficiaries. The research utilizes a qualitative descriptive methodology, with data sourced from an extensive review of relevant literature. The results show that the social assistance program as a means of public economic policy is sufficient to meet the basic needs of the poor. However, it is not yet effective enough, because there are still studies that say that this social assistance has inaccurate targeting of beneficiaries and there are also studies that highlight that this social assistance reduces work motivation and economic independence of the community if it is not balanced with empowerment programs. Therefore, it is necessary to improve public policy, by being more careful in identifying problems, so that it does not often change policies so that this program can be optimally utilized in accordance with its objectives.